Electronic density of states for two-dimensional system in uniform magnetic and Aharonov-Bohm fields - Slobodeniuk, A.O.; Sharapov, S.G.; Loktev, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We study two-dimensional electronic gas (2DEG) in the background of the Aharonov–Bohm and constantmagnetic fields. The problem of ambiguity of the solutions of the Schrödinger equation is investigated by introducing a finite radius of the flux tube, which then set to zero. Wave functions and spectrum of the 2DEG Hamiltonian are used to construct an expression for the local density of states (LDOS). We obtain that LDOS has a depletion near the origin of the vortex and new peaks, which can't be explained by using Landau levels theory.